The Synthesis and Characterization of Poly(methyl methacrylate-tourmaline acrylate) - Yingmo Hu; Xubo Chen; Yunhua Li (Advances in Materials Science and Engineering)
In order to synthesize the tourmaline-containing functional copolymer, the polymerizable organic tourmaline acrylate was prepared by the surface modification on tourmaline powder and then copolymerization with methyl methacrylate to get poly(methyl methacrylate-tourmaline acrylate). The synthetic processes were optimized, and the structures of the as-prepared samples were characterized by IR, SEM, and X-ray fluorescence analysis. The characterization results indicated that the tourmaline has been introduced into the copolymer by means of surface modification with acryloyl chloride and following copolymerization with methyl methacrylate. The results from the negative ions measurement revealed that the amounts of released negative ions from both the modified tourmaline and its copolymer are much larger than that of tourmaline.